Poisoned water : how the citizens of Flint, Michigan, fought for their lives and warned the nation - Cooper, Candy J., 1955-; Aronson, Marc (Bloomsbury Children's Books, 2020)
Provides an in-depth examination of the 2014 Flint, Michigan, water crisis, one of the worst water crises in United States history, that occurred when city officials decided, as a cost-savings measure, to switch city water sources from Lake Huron to the Flint River, causing old pipes to corrode and water to become contaminated with lead. Chronicles the events that led up to the crisis, the toxic effects of the water on Flint residents, and the activists who fought against the city and state government to hold officials accountable.